The use of deep learning for smartphone-based human activity recognition - Stampfler, Tristan; Elgendi, Mohamed; Fletcher, Richard Ribon; Menon, Carlo (Frontiers in Public Health, 2023)
The emerging field of digital phenotyping leverages the numerous sensors embedded in a smartphone to better understand its user’s current psychological state and behavior, enabling improved health support systems for patients. As part of this work, a common task is to use the smartphone accelerometer to automatically recognize or classify the behavior of the user, known as Human Activity Recognition (HAR). In this paper, we present a deep learning method using the Resnet architecture to implement HAR using the popular UniMiB-SHAR public dataset, containing 11,771 measurement segments from 30 users ranging in age from 18 to 60 years. We present a unified deep learning approach based on a Resnet architecture that consistently exceeds the state-of-the-art accuracy and F1-score across all classification tasks and evaluation methods mentioned in the literature. The most notable increase we disclose regards the leave-one-subject-out evaluation, known as the most rigorous evaluation method, where we push the state-of-the-art accuracy from 78.24% to 80.09% and the F1-score from 78.40% to 79.36%. For such results, we resorted to deep learning techniques, such as hyper-parameter tuning, label smoothing, and dropout, which helped regularize the Resnet training and reduced overfitting. We discuss how our approach could easily be adapted to perform HAR in real-time and discuss future research directions.